ANALISIS KONDISI EKONOMI KARET DI BANJARMASIN BERDASARKAN KORAN BINTANG BORNEO TAHUN 1930 - Fathimah Dayaning Pertiwi; Nurkhadijah, Yunita (History Education Department, Universitas Mulawarman, 2022)
Bintang Borneo newspaper is a newspaper that was first published in 1924 in Banjarmasin. Information about the economy is of course important for the people of Kalimantan. One of the characteristics of rubber cultivation in the Banjarmasin area was that it was first started by foreign entrepreneurs, but later on, native planters played an important role. The main livelihood of the people in Banjarmasin in 1930 was rubber plantations. In early 1930 the world economic crisis occurred and had a direct effect on rubber prices and the community's economy.